2022
DOI: 10.1021/acsnano.2c05902
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Assessment of High-Performance Scaled Double-Gate Transistors from Monolayer WS2

Abstract: Scaling of monolayer transition metal dichalcogenide (TMD) field-effect transistors (FETs) is an important step toward evaluating the application space of TMD materials. Although some work on ultrashort channel monolayer (ML) TMD FETs has been published, there exist no comprehensive studies that assess their performance in a statistically relevant manner, providing critical insights into the impact of the device geometry. Part of the reason for the absence of such a study is the substantial variability of TMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Shaded areas represent the most desirable regions of device operation for logic transistors. Data sources: indium oxide, [106,[110][111][112][113] ITO, [100,142,99] IGZO, [143][144][145][146]97] IWO, [102,135] ZnO, [147] MoS 2 , [148][149][150][151][152][153][154][155][156] WS 2 , [157][158][159][160] Te, [161] WSe 2 , [162] black phosphorus, [163][164][165] GaN, [166] InGaAs, [167] InAs, [168] Si. [116] conditions [110] with disadvantages in process maturity, geometry (planar versus fin), and device scaling (40 nm channel length versus the 4 nm-equivalent node).…”
Section: Ultra-high Currentmentioning
confidence: 99%
“…Shaded areas represent the most desirable regions of device operation for logic transistors. Data sources: indium oxide, [106,[110][111][112][113] ITO, [100,142,99] IGZO, [143][144][145][146]97] IWO, [102,135] ZnO, [147] MoS 2 , [148][149][150][151][152][153][154][155][156] WS 2 , [157][158][159][160] Te, [161] WSe 2 , [162] black phosphorus, [163][164][165] GaN, [166] InGaAs, [167] InAs, [168] Si. [116] conditions [110] with disadvantages in process maturity, geometry (planar versus fin), and device scaling (40 nm channel length versus the 4 nm-equivalent node).…”
Section: Ultra-high Currentmentioning
confidence: 99%
“…Furthermore, Sun et al reported that the use of a partially metal covered TG stack results in a more significant shortchannel effect due to the fringing field, in contrast to fully covered TG stack. 24 Figure 2d illustrates the band structure of our novel TG device with a fully metal covered hBN stack achieved through vdW transfer (L tg is approximately 500 nm). Using TG metal electrodes as an etching mask ensures well matching alignment between metal electrode and hBN dielectric, giving rise to effective TG control.…”
mentioning
confidence: 99%
“…To address this limitation, the lateral junction devices are proposed by patterning the doping profile of the channel area, offering improved electrostatic controllability of oxidized WSe 2 FETs through the generation of a built-in potential. ,,, Furthermore, using a top-gate (TG) to modulate the built-in potential can be an effective approach for achieving high-performance p-FETs. , However, achieving a narrow top-gate length ( L tg ) in the R&D environment is challenging when using conventional top-gate fabrication methods that employ oxygen plasma doping at the spacer area. Additionally, challenges are presented when 2D materials are employed as a channel, e.g., transfer of dielectric layer and additional lithographic patterning process to precisely positioning TG electrodes, which limit the yield of fabrication process contributing to realization of high-performance p-FETs and p-type metal-oxide-semiconductor (PMOS) inverter …”
mentioning
confidence: 99%
See 2 more Smart Citations